Pengaruh Trust dan Peran BAZNAS Terhadap Minat Masyarakat Menunaikan Zakat di BAZNAS Sinjai Dengan Penggunaan Teknologi Sebagai Variabel Moderasi - Ismawati Ismawati; Dedy Irwansyah; Nurfiah Anwar; A. Syathir Sofyan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the influence of trust and the role of BAZNAS on the public’s interest in paying zakat through BAZNAS Sinjai, with the use of technology considered as a moderating variable. The research applied a quantitative approach with a correlational/associative design. The population consisted of approximately 251,000 Muslim residents in Sinjai Regency. The sample size was determined using the Krejcie–Morgan formula, while purposive sampling was employed based on predetermined criteria. Respondents were required to be Muslim, reside in Sinjai, and meet the obligations of paying zakat. A total of 226 individuals participated in the study. Data were collected using questionnaires distributed directly and via Google Forms. The analysis was carried out using Structural Equation Modeling with the Partial Least Squares method (SEM-PLS) through SmartPLS 4.0. The findings indicate that trust has a positive and significant effect on the intention to pay zakat through BAZNAS Sinjai. Similarly, the role of BAZNAS shows a significant positive influence on the community’s zakat-paying interest. Furthermore, technology strengthens the relationship between trust and zakat intention, as well as the link between BAZNAS’s role and the intention to fulfill zakat obligations. These results are expected to serve as a reference for relevant institutions in enhancing zakat participation by building trust, optimizing BAZNAS’s functions, and utilizing technology in zakat management.